2021
DOI: 10.1038/s41467-021-25394-w
|View full text |Cite
|
Sign up to set email alerts
|

Completely non-fused electron acceptor with 3D-interpenetrated crystalline structure enables efficient and stable organic solar cell

Abstract: Non-fullerene acceptors (NFAs) based on non-fused conjugated structures have more potential to realize low-cost organic photovoltaic (OPV) cells. However, their power conversion efficiencies (PCEs) are much lower than those of the fused-ring NFAs. Herein, a new bithiophene-based non-fused core (TT-Pi) featuring good planarity as well as large steric hindrance was designed, based on which a completely non-fused NFA, A4T-16, was developed. The single-crystal result of A4T-16 reveals that a three-dimensional inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
254
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 272 publications
(259 citation statements)
references
References 66 publications
3
254
0
2
Order By: Relevance
“…Recently, Hou et al reported a totally unfused SMA named A4T-16, which contains bithiophene-based non-fused core (TT-Pi) with good planarity as well as large steric hindrance. 67 This molecule exhibited a three-dimensional interpenetrating network due to the compact π–π stacking between the adjacent end-capping groups. OSCs based on PBDB-TF:A4T-16 exhibited a high PCE of 15.2% with a FF of 79.8%.…”
Section: The Development Of New Donor and Acceptor Materials In The Oscsmentioning
confidence: 99%
“…Recently, Hou et al reported a totally unfused SMA named A4T-16, which contains bithiophene-based non-fused core (TT-Pi) with good planarity as well as large steric hindrance. 67 This molecule exhibited a three-dimensional interpenetrating network due to the compact π–π stacking between the adjacent end-capping groups. OSCs based on PBDB-TF:A4T-16 exhibited a high PCE of 15.2% with a FF of 79.8%.…”
Section: The Development Of New Donor and Acceptor Materials In The Oscsmentioning
confidence: 99%
“…With the exception of the A-D-D'-D-A-type structure, in light of numerous easily-available electronwithdrawing units, significant attention has been drawn to research into A-D-A'-D-A-type NFRAs featuring electron-withdrawing units as the central core, such as BT [50,58,67] , benzotriazole (BTz) [68][69][70] , benzo-[1,2-c:4,5c']dithiophene-4,8-dione (BDD) [71,72] , benzobis(thiazole) (BBTz) [73] , quinoxaline (Q) [74] , thieno[3,4-c]pyrrole-4,6-dione (TPD) [71,75] , isoindigo (IID) [76] and so on [Figure 4]. Among them, BT and BTz have been widely adopted as A' units to construct NFRAs for their unique merits: (1) quinoidal structures are beneficial for broadening the absorption range; (2) the 5,6-positions of BT and BTz can be readily functionalized; and (3) the N•••S noncovalent interaction can be formed between the BT/BTz core and adjacent thiophene rings.…”
Section: Nfras With A-d-a'-d-a Structurementioning
confidence: 99%
“…After device optimization, a moderate photovoltaic performance of BTCIC-4Cl was achieved, with a PCE of 10.50%, a V OC of 0.75 V and a J SC of 21.00 mA cm -2 . Based on the abovementioned results, Wang et al [58] then systematically investigated the effects of H (BT-IC4F), F (BT2F-IC4F) and alkoxy chains (BTOR-IC4F) at the 5,6-positions of the BT core on the molecular configuration and device performance. The ladder-like molecular structures locked by the N•••S, F•••S and O•••S noncovalent interactions were formed for these acceptors, as suggested by DFT calculations.…”
Section: Nfras With A-d-a'-d-a Structurementioning
confidence: 99%
See 1 more Smart Citation
“…However, such design always involves high synthetic complexity, thereby limiting their further practical applications. In this context, many researchers have paid attention to explore new A-D-A-type NFAs with semi-fused (Li et al, 2018;Huang et al, 2019;Liu X. et al, 2020;Luo et al, 2021) and even fully unfused electronrich cores (Bi et al, 2021;Ma et al, 2021;Wen et al, 2021;Zhou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%